If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -5x = -9 + 1 + 2x + -7 Combine like terms: 4x + -5x = -1x -1x = -9 + 1 + 2x + -7 Reorder the terms: -1x = -9 + 1 + -7 + 2x Combine like terms: -9 + 1 = -8 -1x = -8 + -7 + 2x Combine like terms: -8 + -7 = -15 -1x = -15 + 2x Solving -1x = -15 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -1x + -2x = -15 + 2x + -2x Combine like terms: -1x + -2x = -3x -3x = -15 + 2x + -2x Combine like terms: 2x + -2x = 0 -3x = -15 + 0 -3x = -15 Divide each side by '-3'. x = 5 Simplifying x = 5
| -8c-41=-53-5c | | 8c-41=-53-5c | | 45p=27 | | 6-3n=4n+1+5 | | x*x-5x+4=0 | | 12+5k=3k-3+5 | | 3(2z-1)-3(5-3z)=6 | | 5x^2-25=100 | | -9b-6b=-10b-20 | | 6x=9y | | 6(d-5)+3= | | 4+4n=-4n+6n | | 0.33r+4=1.33r+9 | | 5x+6-(9x-2)= | | 0.33r+4=1.33+9 | | lx+55=154 | | 25+t=25 | | 3w-6=-24 | | X^2-16=15c | | 6+3m=m-2 | | 2x^2-ax+8=0 | | x^2+6-18=0 | | x-34=48 | | 1/3-4/3 | | 1/3r-4/3r | | X^2+36y^2=0 | | 12x^2-3y^2=108 | | 3n-5=-14 | | 5(3c-1)-1=11c+2 | | 2x+x+4x=42 | | 5(3c-1)-1=11c+12 | | (x^-2y^-3)^4(x^2)^-1/2/x^-1/2y^-12 |